Підстави і порядок припинення шлюбно-сімейних правовідносин - Сафончик, О. І.; Сафончик, О. И.; Safonchyk, О. (My University, 2010)
Matrimonial relationship is terminated due to certain life circumstances – legal facts. Essential principles for termination of marriage and family relations are legal facts as follows: 1) the termination of marriage (as a result of its dissolution or by the death of a spouse), 2) termination of the actual marriage. Current family law provides for two orders of divorce: judicial and administrative. Legal registration of the termination of marriage is compulsory for dissolution of marriage, regardless of the question of divorce or the death of a spouse, whereas the termination of actual marital relationship of such registration is not required.
Сафончик О. І. Підстави і порядок припинення шлюбно-сімейних правовідносин / О. І. Сафончик // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 575-583.
Keywords: припинення шлюбно-сімейних правовідносин; судовий та адміністративний порядок розірвання шлюбно-сімейних відносин; юридичне оформлення факта зупинення брака; прекращение брачно-семейных правоотношений; судебный и административный порядок расторжения брачно-семейных отношений; юридическое оформление факта прекращения брака; termination of marriage and family relations; Judicial and administrative procedures for the termination of marriage and family relations; legal registration of the termination of marriage